Structural, electronic, optical, elastic properties and Born effective charges of monoclinic HfO2 from first-principles calculations - 刘其军 张宁超 刘福生 刘正堂 (中国物理B：英文版, 2014)
First-principles calculations of structural, electronic, optical, elastic, mechanical properties, and Born effective charges of monoclinic HfO2 are performed with the plane-wave pseudopotential technique based on the density-functional theory. The calculated structural properties are consistent with the previous theoretical and experimental results. The electronic structure reveals that monoclinic HfO2 has an indirect band gap. The analyses of density of states and Mulliken charges show mainly covalent nature in Hf-O bonds. Optical properties, including the dielectric function, refractive index, extinction coefficient, reflectivity, absorption coefficient, loss function, and optical conductivity each as a function of photon energy are calculated and show an optical anisotropy. Moreover, the independent elastic constants, bulk modulus, shear modulus, Young＇s modulus, Poisson＇s ratio, compressibility, Lam6 constant, sound velocity, Debye temperature, and Born effective charges of monoclinic HfO2 are obtained, which may help to understand monoclinic HfO2 for future work.